Does effective designing of operation theaters contribute towards staff satisfaction: A cross-sectional study. Issue 9 (6th July 2015) - Rinkoo, Arvind Vashishta; Singh, Surendra Pratap; Mishra, Shubhra; Vashishta, Geeta; Chandra, Hem; Singh, P K
Abstract : Purpose: – This study aims to measure the staff satisfaction achieved with regard to the recently furnished modular operation theaters (MOTs). Design/methodology/approach: – A cross-sectional study through questionnaire-based interviews was done. Desired sample size for ANOVA design came out to be 25 per level at a level of significance of 5 per cent and a power of 85 per cent. Findings: – Overall, mean rating of the satisfaction of the staff was 7.52 with a standard deviation (SD) of 2.35. Mean ratings (with standard deviations) of surgeons, nurses and anesthetists were 7.14 (1.26), 7.21 (0.95) and 8.21 (0.48), respectively. One sample t -test showed that all the three categories of staff were satisfied. Post-hoc test revealed that the anesthetists were significantly more satisfied than the surgeons ( p = 0) and the nurses ( p = 0.001). Maximum satisfier was aseptic environment provided by the MOTs. Hatch box with ultraviolet technology also attracted high ratings from all the three categories. Staff considered all the probable advantages of MOTs, except air showers, significant with regard to its satisfaction and morale. Originality/value: – Findings suggest that initiatives such as effectively designed MOTs may contribute toward the satisfaction of all categories of staff working in operation theaters (OTs), which, in turn, may probably lead to better overall performance of these facilities. It is desirable that hospital planners in modern health-care systems give adequate importance to finer aspects of OT designing.